1997
DOI: 10.1159/000266463
|View full text |Cite
|
Sign up to set email alerts
|

Loading Changes in Time-Based Parameters of Glottal Flow Waveforms in Different Ergonomic Conditions

Abstract: The effects of prolonged (5 × 45 min) reading in different environmental and ergonomic conditions on time-based glottal waveform parameters of normal female and male subjects (n = 80) were studied. The exposure groups (n = 5 females and males per cell) consisted of eight combinations of the following factors: (1) normal ( < 65 dB) or high ( > 65 dB) speech output level; (2) sitting or standing posture; (3) low (25 ± 5%) or high (65 ± 5%) relative humidity of ambient air. Two rest (morning and noon) and three l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…The interpretation is speculative because the voice variables were measured on only 1 day, but gets support from Hunter and Titze [23], who reported that teachers still experienced voice symptoms 1 day after the fatiguing activity. Poor working postures especially accumulate loading effects and may cause more obvious impairment later [25]. …”
Section: Discussionmentioning
confidence: 99%
“…The interpretation is speculative because the voice variables were measured on only 1 day, but gets support from Hunter and Titze [23], who reported that teachers still experienced voice symptoms 1 day after the fatiguing activity. Poor working postures especially accumulate loading effects and may cause more obvious impairment later [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Cycle dose (measured in number of accumulated cycles) was originally introduced under the name vocal loading index (Vilkman, Lauri, Alku, Sala, & Sihvo, 1997); it quantifies the total number of oscillatory periods completed by the vocal folds over the exposure time and is obtained as follows:…”
Section: Cycle Dosementioning
confidence: 99%
“…Different phenomena of voice production have been studied by concentrating on issues like phonation type, 17 intensity, 8 voice quality, 18 emotions, 19 pitch, 7,12 disturbed voice functions, 10,[20][21][22][23][24][25] singing styles, 16,[26][27][28] and vocal loading. 9,29,30 In addition, some studies have discussed IF from a methodological point of view. 6,31 Given the prevalence of IF in the field of voice science, it is surprising that the differences between IF methods have not yet been studied extensively.…”
Section: Introductionmentioning
confidence: 99%